PFAS Exposure in Consumer Products and the Risk of Recurrent Miscarriage: A Clinical Study and Health Policy Implications - Eva Fauzia (Al Makki Health Informatics Journal, 2025)
Exposure to Per- and Polyfluoroalkyl Substances (PFAS) from everyday consumer products has become a global issue of concern due to its persistent chemical properties and negative impact on reproductive health. This study aims to analyze the association between PFAS exposure and the risk of recurrent miscarriage in women of reproductive age in urban areas of Indonesia and examine the implications of public health policies. The research method uses a qualitative approach with a clinical case study design. Data were collected through in-depth interviews with hospital management, questionnaires to licensed medical personnel, field observations in respondents' households, and analysis of medical documents. The results showed that the majority of respondents were exposed to PFAS through various channels, such as the use of non-stick pans (73%), the consumption of fast food with plastic-coated packaging (67%), household cleaning products (80%), and drinking water in plastic packaging (100%). Interviews with hospital management indicate an increase in cases of recurrent miscarriages that cannot be medically explained, while medical personnel emphasize the need for PFAS regulation. These findings are in line with global research, but reveal gap research and gap policies in Indonesia. This study emphasizes the urgency of integrating environmental factors in clinical assessments and the preparation of national regulations to reduce PFAS exposure, as well as providing practical recommendations for the public in choosing safer products.